IMPROVING REMOTE BANKING SERVICES – PROMOTING OPTIMAL CUSTOMER SATISFACTION - Karimova Aziza , Makhomadrizoevna; Tursunov Faridun , Mustafoevich (THE INNOVATION ECONOMY, 2025)
This article discusses issues related to the strategy of improving banking services and increasing customer satisfaction. The focus is on technological advancements, personalized experiences, effective communication, reliable security measures, and sustainable practices. It also analyzes key areas where improvements can be made, and offers insights into how banks can leverage technology, facilitate personalized interactions, optimize communication, enhance security, and ensure resilience to create a more enriching banking experience for customers.